Part 1: Design, modeling and simulation of post-combustion CO2 capture systems using reactive solvents. Issue 3 (June 2011) - Liang, Zhiwu Henry; Sanpasertparnich, Teerawat; Tontiwachwuthikul, Paitoon PT; Gelowitz, Don; Idem, Raphael
The simulation and modeling of post-combustion CO2 capture systems are considered to be an important strategy to obtain process integrity and gain design confidence for the construction and commissioning of commercial post-combustion CO2 capture plants. It is therefore essential to obtain an understanding of the fundamental concepts of designing and modeling. This article reviews the concepts of designing a CO2 capture system with specific emphasis on the absorber for diameter and height. It covers several steps (i.e., empirical design method, theoretical design method, laboratory method and pilot plant techniques) used to design the absorber. A conceptual design of an overall CO2 capture process is also given in the article. Process validations of the modeling using ProMax with four existing pilot plants. (the International Test Centre of CO2 Capture pilot plant, the Esbjerg CASTOR pilot plant, the Institute of Thermodynamics and Thermal Process Engineering, Stuttgart pilot plant and the SINTEF/NTNU pilot plant) are presented. Moreover, a discussion of process integration of the CO2 capture plant into a fossil fuel-fired power plant is included in this paper.